Effect of Jaw Thrust and BURP Maneuvers on Glottis Visualization During C-MAC® Videolaryngoscopy - Mohseni, Masood; Seyed Siamdoust, Alireza; Rokhtabnak, Faranak; Rezghi, Marjan; Koleini, Zahra Sadat (Annals of Anesthesiology and Critical Care, 2017)
Background: Different techniques are proposed to improve glottis visualization during laryngoscopy, namely backward-upwardrightward pressure (BURP) and jawtrust; however, with controversial results. The current study aimed at comparing the maneuvers to elicit their efficacy for better glottis visualization in videolaryngoscopy (VL). Methods: In the current self-controlled, randomized, clinical trial, 104 patients candidate for elective surgery requiring endotracheal intubation were recruited. All participants underwent airway examination, thyromental distance (TMD), limitedmouthopening, and head extension were recorded. Laryngoscopy was performed by a single anesthetist using C-MAC® (KARL STORZ, Germany) and a Macintosh blade, size 4. A second anesthetist applied BURP and jaw thrust maneuvers. For each patient 3 images were provided with and without a maneuver in the optimal view. The images were randomly coded. An anesthesiologist blinded to the codes and assignments scored images based on the Cormack-Lehane scoring system. Results: Both maneuvers significantly improved glottis visualization, but BURP rendered more promising effects. Gender-specific analyses yielded similar results. In subgroups of patients with limited head extension, TMD < 5 cm or limited mouth opening, the findings were significant. Conclusions: Both BURP and jaw thrust maneuvers resulted in better glottis visualization. Nevertheless, BURP may provide better conditions during laryngoscopy irrespective of airway parameters and should be attempted first